1998
DOI: 10.1136/sti.74.2.128
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection and high risk behavior among patients attending an STD referral clinic in Prague, Czech Republic

Abstract: Objective: This survey was conducted to determine the prevalence of HIV infection and associated risk behaviour in a high risk population of clients attending an STD clinic in Prague, Czech Republic. Methods: Between September 1994 and January 1995 clients entering the Apolinar STD clinic in Prague, Czech Republic, were enrolled in a blinded, unlinked HIV antibody seroprevalence study. Non-identifying demographic characteristics, STD diagnoses, HIV risk exposures, and voluntary HIV testing experience were extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In our study, 8% have a C trachomatis infection, compared to rates between 6% in Tanzania and 13% in Cape Verde [13,22]. Gonorrhea is found in 3% of the women, compared to rates that range from 2% in Gabon to 8% in South Africa [16,21]. Although difficult to measure, it is likely that complications and sequelae due to these infections among pregnant women and their infants in sub-Saharan Africa are substantial.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In our study, 8% have a C trachomatis infection, compared to rates between 6% in Tanzania and 13% in Cape Verde [13,22]. Gonorrhea is found in 3% of the women, compared to rates that range from 2% in Gabon to 8% in South Africa [16,21]. Although difficult to measure, it is likely that complications and sequelae due to these infections among pregnant women and their infants in sub-Saharan Africa are substantial.…”
Section: Discussionmentioning
confidence: 77%
“…As screening with specific diagnostic tests have been out of reach, risk scores based on sociodemographic risk factors, symptoms or signs of infection, urine sticks and microscopy have been explored as screening tools to identify asymptomatic infections among pregnant women. Studies from sub-Saharan countries have shown variable and unconvincing results [9,10,13-16]. …”
Section: Introductionmentioning
confidence: 99%
“…3 A low HIV prevalence (0.2%) has been previously reported among young IDUs in the city of Prague in 1998. 9 The one HIVinfected subject among IDUs found in our study was a young, 20-year-old Czech heterosexual from the city of Prague, who reported using heroine and pervitin (a variety of methamphetamine, also called "Czecho"). This suggests that the HIV epidemic situation in the Czech Republic seems to be stable and low among IDUs for now.…”
mentioning
confidence: 70%
“…8 High-risk behaviors, such as unsafe sexual practices, may contribute to the rapid transmission of HIV in this high-risk group. 9 As in other European countries, the risk of HIV has been previously associated with a history of homosexual/bisexual behavior, which is estimated to constitute the predominant risk category. In the Czech Republic, the majority of recorded HIV-infected persons are from the city of Prague, principally among homosexuals/bisexuals.…”
mentioning
confidence: 99%
“…Although the rates of HIV infection are low at this time, unsafe sexual practices may be common, especially among teenagers. Data on sexual behaviour in Hungary are not readily available, but other Eastern European countries have recently witnessed increases in the incidence of sexually transmitted diseases (STDs) and risky behaviours, and teenagers are especially at high risk of becoming infected (Hegyi et al, 1997;Tichonova et al, 1997;Mikl et al, 1998). For example, three-quarters of heterosexual patients at an STD clinic in Prague, Czech Republic, had had unprotected sex, about 11% of heterosexual men had had sex with prostitutes, and the same percentage of women had engaged in prostitution.…”
Section: Introductionmentioning
confidence: 99%